The Impact of Health Literacy on Medication Adherence and Acceptance in COVID-19 Patients With Home Monitoring - Demir Bozkurt, Feyza; Onder, Cicek; Yildizdal, Cumali; Ardic, Aysun; Bozkurt, Feyza Demir (Wiley, 2025)
Background: Health literacy plays a critical role in ensuring adequate medication adherence and acceptance, especially during pandemics like COVID-19, where misinformation is prevalent.Objective: To evaluate the relationship between health literacy levels, medication adherence, and acceptance among COVID-19 patients managed with home-based treatment protocols.Methods: This study was conducted through an online questionnaire with a random sampling method. Data were collected using the Identifying Characteristics Form and the Turkish Health Literacy Scale, and 279 COVID-19 patients were included in this study. Descriptive and correlation statistics were used to analyze the data.Results: The results showed that 72.8% of the patients used drugs, and the drug use level was also high. In examining the relationship between COVID-19 drug therapy and the participants' health literacy, the total score of the Turkish Health Literacy Scale, the Treatment and Service subscale score, and the Preventing Diseases and Promoting Health subscale score were found to be significantly higher.Conclusion: While adequate health literacy was noted among the participants, its impact on medication acceptance was insignificant. Further research is warranted to identify additional factors influencing adherence and acceptance of treatment protocols during public health crises like COVID-19.
Keywords: Covid-19; Drug Acceptance; Health Literacy; Medication Adherence; Sars-Cov-2